2020
DOI: 10.1002/ar.24516
|View full text |Cite
|
Sign up to set email alerts
|

Microarchitecture of the hearts in term and former‐preterm lambs using diffusion tensor imaging

Abstract: Diffusion tensor imaging (DTI) is an MRI technique that can be used to map cardiomyocyte tracts and estimate local cardiomyocyte and sheetlet orientation within the heart. DTI measures diffusion distances of water molecules within the myocardium, where water diffusion generally occurs more freely along the long axis of cardiomyocytes and within the extracellular matrix, but is restricted by cell membranes such that transverse diffusion is limited. DTI can be undertaken in fixed hearts and it allows the three‐d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…If confirmed in humans, fibrosis-associated stiffness could explain the observed differences in diastolic KE. Another possible physiologic mechanism affecting diastolic function could be myocardial fiber orientation (44), although more data are needed in this area in animals and humans. Further investigation into the mechanisms of altered RV diastolic function in the human preterm heart will be required to assess the role of increased myocardial stiffness and fibrosis, as well as myocyte-level dysfunction, such as impaired calcium handling.…”
Section: Discussionmentioning
confidence: 99%
“…If confirmed in humans, fibrosis-associated stiffness could explain the observed differences in diastolic KE. Another possible physiologic mechanism affecting diastolic function could be myocardial fiber orientation (44), although more data are needed in this area in animals and humans. Further investigation into the mechanisms of altered RV diastolic function in the human preterm heart will be required to assess the role of increased myocardial stiffness and fibrosis, as well as myocyte-level dysfunction, such as impaired calcium handling.…”
Section: Discussionmentioning
confidence: 99%
“…30 In a recent diffusion tensor imaging study by our laboratory, we showed that LV wall volume, cavity volume, length, and lateral wall width did not differ between former-preterm lambs and lambs born at term, by 5 months' TEA. 41 Similarly, an echocardiographic study showed that although body mass index and body surface area were reduced in 6-year-old children born extremely preterm compared with age-matched term controls, LV mass was unaffected after adjusting for body surface area. 40 However, LV length, width, and aortic valve annulus diameter were 3-5% smaller in the preterm group; this was associated with impaired LV systolic function.…”
Section: Preterm Birth Reduced Body Weight But Did Not Affect Heart Growthmentioning
confidence: 96%
“…Animal models and histomorphological studies have shown that the premature interruption of cardiac growth leads to cellular changes in the myocardium. In different reports on preterm‐born sheep, the myocardium was characterized by hypertrophied cardiomyocytes in both ventricles (Bensley et al, 2010), alterations in the extracellular compartment (Le, Ferreira, et al, 2021), and an increase in interstitial collagen deposition (Bensley et al, 2010; Le, Dahl, et al, 2021). Similarly, in a rat model of neonatal hyperoxia exposure to mimic preterm birth‐related conditions, the cardiomyocytes are hypertrophied and there is greater interstitial fibrosis, with in vivo signs of left ventricular (LV) dysfunction by echocardiography (Bertagnolli et al, 2014).…”
Section: The Fetal‐to‐neonatal Transition and The Preterm Heartmentioning
confidence: 99%